Phenomenological Study of Fatherlessness in the Lives of Daughters - Pratiwi, Mutia Rahmi; Yusriana, Amida; Poernomo, Moudy (Faculty of Social and Political Sciences, Universitas Diponegoro, 2024)
In a family, both the mother and father’s roles are equally important. A father's role goes beyond being the breadwinner or the head of the family; he is also expected to play a complete role in supporting a child's development and sharing responsibilities with the mother as a wife. When a father doesn't fulfill his role effectively, the issue of